(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Poultry-related foods are consumed as good and cheap sources of protein globally. This research investigated the levels of Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn in poultry feeds, water samples, and broilers obtained from poultry farms randomly sampled within Uyo Metropolis. These poultry-related products were obtained, treated, and analysed spectrophotometrically using standard analytical techniques. Results showed that, the concentrations of all the metals in poultry feeds and broiler meat were within their recommended limits however, mean levels of Cd and Fe in water sample was higher than their permissible limits. Concentrations in poultry feeds were generally higher than their levels in broiler meat. Multivariate analyses indentified varied factors responsible for the accumulation of these metals in feeds, water samples, and broiler meat examined. The estimated daily intake (EDI) of Cd, Fe, and Zn were higher than their oral reference doses (Rfds) for both the children and adults’ populations. The hazard quotients (HQ) of Cd, Fe, Pb, and Zn for both populations were also higher than one (1). The hazard index of the metals for populations were higher than one but, the children class were more susceptible to non-carcinogenic risks. The incremental lifetime cancer risk (ILCR) for the carcinogens varied between medium to very high cancer risk classes. The total cancer risk (TCR) for the children and adults’ populations were 1.54E-01 and 1.43E-01, respectively higher than the standard limits. The relative risk (RR) analysis identified Cd as metal with the highest potential to cause cancer and non-cancer risks in the consumers of broiler meat from the studied poultry farms. This study has indicated the significance of assessing poultry feeds and related products to establish to the quality.